Chemistry and biology of reactive species with special reference to the antioxidative defence status in pancreatic β-cells - Lenzen, Sigurd (Biochimica et biophysica acta. General subjects, 2017)
Diabetes mellitus is a serious metabolic disease. Dysfunction and subsequent loss of the β-cells in the islets of Langerhans through apoptosis ultimately cause a life-threatening insulin deficiency. The underlying reason for the particular vulnerability of the β-cells is an extraordinary sensitivity to the toxicity of reactive oxygen and nitrogen species (ROS and RNS) due to its low antioxidative defense status. This review considers the different aspects of the chemistry and biology of the biologically most important reactive species and their chemico-biological interactions in the β-cell toxicity of proinflammatory cytokines in type 1 diabetes and of lipotoxicity in type 2 diabetes development. The weak antioxidative defense equipment in the different subcellular organelles makes the β-cells particularly vulnerable and prone to mitochondrial, peroxisomal and ER stress. Looking upon the enzyme deficiencies which are responsible for the low antioxidative defense status of the pancreatic β-cells it is the lack of enzymatic capacity for H2O2 inactivation at all major subcellular sites. Diabetes is the most prevalent metabolic disorder with a steadily increasing incidence of both type 1 and type 2 diabetes worldwide. The weak protection of the pancreatic β-cells against oxidative stress is a major reason for their particular vulnerability. Thus, careful protection of the β-cells is required for prevention of the disease. •The β-cell is particularly vulnerable to oxidative stress due to its low antioxidative defense status.•Oxidative stress causes β-cell dysfunction in type 1 and type 2 diabetes.•Mitochondrial, peroxisomal and ER stress contribute to the diabetic metabolic state.•Mitochondria and peroxisomes are major sites of ROS generation in the β-cells.•ROS generation in the ER is important for proinsulin folding stress manifestation.